Hydrolyzed hemp seed proteins as bioactive peptides - Hadnađev Miroslav; Dizdar Manda; Hadnađev-Dapčević Tamara; Jovanov Pavle; Mišan Aleksandra; Sakač Marijana (Journal on Processing and Energy in Agriculture, 2018)
Hemp seed cake, a by-product of cold oil processing, represents a food waste material of high nutritional value. Therefore, in this research, it was used as starting raw material for bioactive peptides production. Alkali extraction followed by isoelectric precipitation was employed for hemp protein isolation. Subsequently, the influence of different enzymes (alcalase and pancreatin), as well as the degree of hydrolysis on the kinetics of different molecular weights peptides production and their antioxidant potential was investigated. The DPPH• scavenging activity of hemp protein hydrolysates and hemp protein isolate and their reducing power was determined. The obtained results showed that the strongest antioxidant activity exhibited peptides characterized by the highest degree of hydrolysis. In general, it was concluded that the properties of the obtained hydrolysates were dependent on the type and specificity of the employed protease, as well as the hydrolysistime.